THE PROJECT MANAGEMENT STRATEGY OF ORGANIZATIONS IN THE FIELD OF E-COMMERCE - A. V. Gorkusha; Ju. I. Enin (Цифровая трансформация, 2018)
The article substantiates the importance of the project approach and a strategy in the management process. The specific of the formation of a management strategy in conditions of eCommerce has been considered. The main features of the stages of the eCommerce project implementation has been obtained. The characteristics of the main working groups (teams) that require organization and coordination in the process of e-Commerce project managing has been given.